PERANCANGAN SISTEM PENGUKURAN KINERJA PADA PDAM LUMAJANG DENGAN BALANCED SCORECARD - Titisari, Manik Ayu (JURNAL TEKMAPRO, 2006)
Abstract . PDAM of Lumajang is one of the Local Owned Business Institutions which offer public services of running water. Performance Measurement System which is applied refers to a system stated in the Department of Internal Affairâs Decision No. 47/1999 which is still based on the firmâs financial performance so that it does not reflect all its activities. Besides, all PDAMs should implement this performance measurement system, but each PDAM has its own visions, missions, and strategies. Howefer, a good performance measurement system must reflect performances of all activities in the related firm. Thus, in order to get the comprehensive performance measurement system, it should be a system which is able to represent the whole firmâs performances, namely Balanced Scorecard. Performance Measurement System using the Balanced Scorecard model is based on the Balanced Scorecard frameworks, that are determination of measurement architecture, determination of strategic objectives of each perspective (financial, customer, internal business process, learning and growing), determination of Key Performance Indicators (KPI), and determination of targets and initiatives (act of planning). Based on the analysis results, the following are performances of PDAM Lumajang in 2003 in terms of each perspective : the Financial Perspektive is 1.967Â  , the Customer Perspektive is 1.08Â  , the Internal Business Process Perspektive is 1.331 , and the Learning and Growing Perspektive is 0.64. Thus, in a whole the performances of PDAM Lumajang is good enough with the performance value of Â 5.02 . Keywords : Performance Measurement System, Balanced Scorecard, Local Owned Business Institutions Intisari . PDAM TK II Lumajang adalah salah satu Badan Usaha Milik Daerah (BUMD) yang memberikan jasa pelayanan di bidang air minum. Sistem Pengukuran Kinerja (SPK) yang digunakan selama ini adalah sistem pengukuran kinerja yang tertuang dalam Keputusan Menteri Dalam Negeri No.47 Th 1999 yang masih banyak bertumpu pada kinerja keuangan perusahaan sehingga belum memperlihatkan kinerja dari aktivitas-aktivitas perusahaan secara keseluruhan. Dalam menerapkan sistem penilaian kinerja masing-masing PDAM pada dasarnya memiliki visi, misi, dan strategi yang berbeda-beda. Sistem pengukuran kinerja yang baik adalah sistem yang merupakan penjabaran visi, misi, dan strategi perusahaannya dan mampu memperlihatkan kinerja dari aktivitas-aktivitas perusahaan tersebut secara keseluruhan. Proses perancangan SPK dengan model Balanced Scorecard didasarkan pada langkah-langkah (framework) dari Balanced Scorecard, yaitu penetapan arsitektur pengukuran, penentuan tujuan strategis (strategic objectives) dari masing-masing perspektif (finansial, pelanggan, proses bisnis internal, belajar dan tumbuh), penentuan Key Performance Indicators (KPI) dan penentuan target serta inisiatif (rencana aksi). Dari hasil analisa diperoleh kinerja PDAM Lumajang tahun 2003 untuk masing-masing perspektif adalah sebagai berikut : Perspektif Finansial sebesar 1,967 , Perspektif Pelanggan sebesar 1,08 , Perspektif Proses Bisnis Internal sebesarÂ  1,331Â  , Perspektif Belajar dan Tumbuh sebesar 0,64Â  Dengan demikian secara keseluruhan, kinerja PDAM Lumajang adalah cukup baik dengan nilai kinerja sebesar 5,02. Kata kunci : Sistem Pengukuran Kinerja, Balanced Scorecard, BUMD